Bactericidal/Permeability-Increasing Protein (BPI), a Novel Antimicrobial Molecule in Human Breast Milk with Immune Potential - Alba Soledad Aquino-Domínguez; María de los Ángeles Romero-Tlalolini; Honorio Torres-Aguilar; Juan Carlos Rodríguez-Alba; Lucia Lourdes Martínez-Martínez; Francisco Javier Sánchez-Peña; María Teresa Hernández-Huerta; Jesús Elizarrarás-Rivas; Gabriela Tapia-Pastrana; Melisa Gómez-López; Elsa Cruz-Martínez; Uriel Eleazar Hernández-Corrales; et al. (Microorganisms)
Breast milk is a fluid of vital importance during the first stages of life of the newborn since, in addition to providing nutrients, it also contains cells and molecules of the immune system, which protect the neonate from infection and, at the same time, modulate the establishment of the microbiota. Bactericidal/permeability-increasing protein (BPI) is relevant in preventing disease and sepsis in neonates. Therefore, the following work aimed to demonstrate the presence of BPI in the different stages of breast milk and its possible immune functions. Our results demonstrate for the first time the presence of soluble BPI and leukocytes and epithelial cells containing it, primarily in the colostrum stage. Using BPI at concentrations typical of colostrum, we observed that it reduces the growth of two distinct E. coli strains, enhances the uptake of these bacteria by monocytes, and suppresses the secretion of the proinflammatory cytokine interleukin (IL)-8 in infected intestinal cells. These findings suggest that BPI transferred via colostrum from mother to newborn may play a significant role in providing antimicrobial and anti-inflammatory protection during the early stages of life.